Germany's healthcare system: funding, resource allocation, provider payment, efficiency, and access - Michaeli, Daniel; Yagmur, Hasan; Michaeli, Christoph T. (SSRN, 2022)
Germany’s healthcare system is praised as one of the best in the world. In this article, we review Germany’s health system by critically analysing its structure, funding, resource allocation, provider payments, efficiency, health outcomes, and access. Whilst health provision and access are comparably high, signs of technical inefficiencies exist. Although health expenditures are rising, outcomes remain average. The co-existence of social and private health insurance leads to inequality in access (preferential treatment) and outcomes. This parallel structure and numerous federal agencies further increase administrative burdens and unavoidably costs. Autonomous self-governing bodies within the well-designed legal framework ensure a balanced competitive healthcare system. Recent regulations reformed long-term care, increased retirement age, and promote prevention and eHealth, besides aiming to introduce pay-for-performance in hospitals